Penerapan Pembelajaran Core Berbantuan LKPD Berbasis Kultural Untuk Meningkatkan Kemampuan Berpikir Kritis - Putri, Ika Mariana; Rahaju, Endah Budi; Hidayat, Taufik (Unika Santu Paulus Ruteng, 2024)
This research is a class action research (CAR). This research aims to improve students’ critical thinking skills by applying CORE learning (Connecting, Organizing, Reflecting, and Extending) through cultural worksheet. This research was conducted at SMPN 2 Kertosono in May 2023. The subject in this research were 7G class students, totaling 32 students. The instrument that used in this research is a matter of critical thinking skills test. The data collection technique used is through a critical thinking ability test. Critical thinking indikators that used in this research are interpretation, analysis, evaluation and inference. The result of this research indicated that implementation CORE learning through cultural worksheet can improve students’ critical thinking skills. This can be seen from the number of students who are able to achive indikators of critical thinking has increased from initial data to cycle 2. Based on the percentage increase in the number of students who achieve indikators of critical thinking from initial data to cycle 2 the percentage of students who achieve interpretation indikators has increased by 50%. The percentage of the number of students who reached the analysis indikators increased by 78%. The percentage of the number of students who reached the evaluation indikator increased by 59%. The percentage of the number of students who achieve the inference indikator has increased by 25%.